Eksistensi Lembaga Pondok Pesantren sebagai Pusat Pendidikan Karakter - Suriyati; Mustamir; Muammanah; Agus, Ricky Wahyudi (Faculty of Tarbiyah and Teacher Training, 2024)
This study discusses the existence of Islamic boarding school education space to become a center for children's character education. This study uses a library research type. This type of research is used to examine and summarize previously existing theories and then reveal theories related to the research title discussed in several points. The discussion points in this article are: first, the definition of Islamic boarding schools; second, the existence of Islamic boarding schools in Indonesia; third, the basic concept of character education; and fourth, Islamic boarding schools as a center for character education. After conducting a more in-depth theoretical study, the results are presented. The study results show that Islamic boarding school educational institutions, namely the first Islamic educational institutions in Indonesia, from their inception until now, have played an important role in shaping students' character by integrating Islamic and cultural values ​​into the learning process. Islamic boarding schools are designed to foster strong and steadfast character in students by emphasizing moral education and religious knowledgeThis study discusses the existence of Islamic boarding school education space to become a center for children's character education. This study uses a library research type. This type of research is used to examine and summarize previously existing theories and then reveal theories related to the research title discussed in several points. The discussion points in this article are: first, the definition of Islamic boarding schools; second, the existence of Islamic boarding schools in Indonesia; third, the basic concept of character education; and fourth, Islamic boarding schools as a center for character education. After conducting a more in-depth theoretical study, the results are presented. The study results show that Islamic boarding school educational institutions, namely the first Islamic educational institutions in Indonesia, from their inception until now, have played an important role in shaping students' character by integrating Islamic and cultural values ​​into the learning process. Islamic boarding schools are designed to foster strong and steadfast character in students by emphasizing moral education and religious knowledge.